PENGEMBANGAN E-MODUL FLIPBOOK INTERAKTIF BERBASIS PROBLEM BASED LEARNING PADA KONSEP MOL - Syarifudin, Syarifudin; Fadhilah, Raudhatul; Kurniasih, Dedeh (FKIP UM Pontianak, 2025)
The results of interviews show that students are less enthusiastic about learning chemistry in class due to uninteresting and boring methods, especially lectures in class which are outdated. With the ever-evolving technology, teachers have the opportunity to increase students' interest in learning through the development of more interesting and relevant learning methods. This study aims to create a valid and practical interactive electronic module based on problem-based learning of class X molecular concepts at SMAN 1 Salatiga. The development model applied in this study is the 3D model which is a modification of the 4D model recommended by Thiagarajan. The sample used in this study was class XC consisting of 35 students. Data collection methods through interviews and indirect communication using research instruments in the form of questionnaires. The results of the analysis showed that the PBL-based electronic interactive flipbook module developed met the validation criteria with an average value of 82.05%. In terms of practicality, responses from teachers and students showed an average value of 85.47%, with a very good assessment. Thus, the developed electronic module can be used as a feasible additional learning resource for grade X students and teachers who teach Chemistry subjects in high school.